A broadly neutralizing human monoclonal antibody against the hemagglutinin of avian influenza virus H7N9. Issue 7 (5th April 2022) - Li, Jingxin; Zhang, Li; Bao, Linlin; Wang, Yuxiao; Qiu, Lin; Hu, Jialei; Tang, Rong; Yu, Huiyan; Shan, Jun; Li, Yan; Qin, Chuan; Zhu, Fengcai
Abstract: Background: The new emerging avian influenza A H7N9 virus, causing severe human infection with a mortality rate of around 41%. This study aims to provide a novel treatment option for the prevention and control of H7N9. Methods: H7 hemagglutinin (HA)-specific B cells were isolated from peripheral blood plasma cells of the patients previously infected by H7N9 in Jiangsu Province, China. The human monoclonal antibodies (mAbs) were generated by amplification and cloning of these HA-specific B cells. First, all human mAbs were screened for binding activity by enzyme-linked immunosorbent assay. Then, those mAbs, exhibiting potent affinity to recognize H7 HAs were further evaluated by hemagglutination-inhibiting (HAI) and microneutralization in vitro assays. Finally, the lead mAb candidate was selected and tested against the lethal challenge of the H7N9 virus using murine models. Results: The mAb 6-137 was able to recognize a panel of H7 HAs with high affinity but not HA of other subtypes, including H1N1 and H3N2. The mAb 6-137 can efficiently inhibit the HA activity in the inactivated H7N9 virus and neutralize 100 tissue culture infectious dose 50 (TCID50 ) of H7N9 virus (influenza A/Nanjing/1/2013) in vitro, with neutralizing activity as low as 78 ng/mL. In addition, the mAb 6-137 protected the mice against the lethal challenge of H7N9 prophylactically and therapeutically. Conclusion: The mAb 6-137 could be an effective antibody as a prophylactic or therapeutic biological treatment for the H7N9 exposure or infection.